Corneal haze in course of Fuchs' endothelial dystrophy - Pescosolido, N; Komaiha, C; Dapoto, L; Lenarduzzi, F; Nebbioso, M (Clinica terapeutica, 2012)
This article describes the observations obtained with confocal microscopy (CM) on the corneal structure in course of corneal edema in a patient with Fuchs endothelial corneal dystrophy (FD). The patient was a 40 year old male, suffering from second stage FD, in course of corneal edema and bullous keratopathy. The tissue structure was analyzed with CM confoscan CS4 (Nidek Technologies(®), Birmingham, UK) using the 40x mode. The CM has shown the presence of gaps due to corneal edema and a diffuse stromal hyper reflectivity related to the alteration of the extracellular matrix. It has also showed the presence of binucleate cells, assimilable to keratocytes, in cytokinesis which presented a typical fusiform aspect with two highly reflective nuclei awaiting cell division. The total number of cells was much lower than that of healthy control subjects of similar age, sex and race. The CM in this case suggests a significantly lower number of cells, presumably keratocytes, compared to normal range, but mostly it shows the presence of cells undergoing cytokinesis, which witnesses the active processes of collagenogenesis and possible vasculogenesis that represent early stages of loss of the normal corneal transparency.